A response surface optimized nanofiltration-based system for efficient removal of selenium from drinking Water. (February 2020) - Malhotra, Meenakshi; Pal, Madhubonti; Pal, Parimal
Graphical abstract: Highlights: Nanofiltration in flat sheet cross module applied in selenium removal. Highest ever simultaneous flux (140 LMH) and rejection (>98%) achieved. First response surface optimized nanofiltration over the highest duration done. The investigated system established as efficient yet low cost selenium removal technology. Abstract: Selenium has been emerging as a serious health hazard due to presence in groundwater used as source of potable water in several regions of the world. Concentration of selenium in such contaminated water is sometimes as high as 400–700 μg/L. Removal of selenium from such water to the safe level of40 μg/l is a big challenge to the scientific community. Selenium was efficiently removed from live contaminated groundwater in this study, by flat sheet cross flow nanofiltration membrane modules under response surface optimized conditions. The governing parameters such as pH, feed dilution, cross flow rate and trans-membrane pressure were optimized. Through judicious selection of membrane, module and operating conditions, a low cost yet efficient nanofiltration-based process for selenium removal has been developed. The novel process uses commercial polyamide nanofiltration membrane in flat sheet and cross flow module that yields a sustainable pure water flux of around 140 L/(m 2 h) at only 14 bar pressure while removing above 98% of selenium from contaminated water under response surface optimized conditions. Thus potential of a novel nanofiltration membrane-based process and system is established which is scalable and can be quickly adopted in offering relief to the suffering milieu.